Chemical composition, in vitro antioxidant and antibacterial activities of Centaurea resupinata subsp. dufourii (dostál) greuter - Bouzghaia, Badra; Ben Moussa, Mohammed; Goudjil, Rima; Hassina Harkat; Patrick Pale (Natural Product Research, 2021)
The current study focuses on the chemical composition, and evaluation of antioxidant and antibacterial activity of the aerial parts of Centaurea resupinata subsp. dufourii. Using different chromatographic methods nine compounds 1–9 were isolated. The structural identification of isolated compounds was achieved using several spectroscopic methods NMR techniques (1H NMR, 13C NMR, COSY, HSQC, HMBC) and mass spectroscopy (ESI-MS) and by comparison with literature data. The structures of these compounds were identified as nicotiflorin (1), apigetrin (2), chrysoeriol (3), apigenin (4), chrysin (5), daucosterol (6), β-sitosterol (7), taraxastrerol (8) and lupeol (9). The antibacterial and antioxidant activities of ethyl acetate and n-butanol extracts have been evaluated. The antioxidant activity was assessed in vitro using DPPH radical scavenging method, which showed that ethyl acetate extract possessed an interesting antioxidant potential (IC50 = 36.263 ± 0.005 μg/mL).   <img alt="Graphical abstract" height="201" id="UF0001image" src="https://www.tandfonline.com/na101/home/literatum/publisher/tandf/journals/content/gnpl20/2021/gnpl20.v035.i22/14786419.2020.1715397/20211119/images/medium/gnpl_a_1715397_uf0001_c.jpg" width="500">